Understanding NSAID-Induced Skin Reactions: Implications for Patient Care - Hasanah; Saidah Nurmala; Harrison (International Journal on ObGyn and Health Sciences, 2024)
Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are commonly prescribed medications used to alleviate pain, inflammation, and fever. However, their widespread use is often accompanied by the risk of adverse drug reactions, including cutaneous hypersensitivity reactions. This research aims to investigate the epidemiology, underlying mechanisms, and implications for patient management in individuals experiencing NSAID-induced skin reactions. Through a comprehensive review of literature and analysis of clinical data, this study provides insights into the incidence, clinical characteristics, and risk factors associated with NSAID-induced skin reactions. Findings reveal a spectrum of adverse events, ranging from mild erythematous rashes to severe cutaneous adverse reactions such as Stevens-Johnson syndrome and toxic epidermal necrolysis. Risk factors including advanced age, female gender, atopy, genetic polymorphisms, and NSAID class are identified, highlighting the importance of personalized risk assessment in clinical practice. Potential mechanisms underlying NSAID-induced skin reactions are elucidated, encompassing dysregulation of cyclooxygenase enzymes, altered production of pro-inflammatory mediators, immunological dysregulation, genetic predisposition, and oxidative stress. Understanding these mechanisms is critical for guiding targeted therapeutic interventions and optimizing patient care. Implications of study findings for clinical practice and patient management are discussed, emphasizing the need for individualized treatment regimens, patient education, multidisciplinary collaboration, and pharmacovigilance.